2008
DOI: 10.1096/fj.08-121384
|View full text |Cite
|
Sign up to set email alerts
|

Downregulation of microRNA expression in the lungs of rats exposed to cigarette smoke

Abstract: Although microRNAs have been investigated extensively in cancer research, little is known regarding their response to noxious agents in apparently healthy tissues. We analyzed the expression of 484 miRNAs in the lungs of rats exposed to environmental cigarette smoke (ECS) for 28 days. ECS down-regulated 126 miRNAs (26.0%) at least 2-fold and 24 miRNAs more than 3-fold. We previously demonstrated that 107 of 4858 genes (2.9%) and 50 of 518 proteins (9.7%) were up-regulated by ECS in the same tissue, which is co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

32
340
2
3

Year Published

2010
2010
2016
2016

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 393 publications
(386 citation statements)
references
References 42 publications
32
340
2
3
Order By: Relevance
“…Last, we found that a greater number of miRNAs were down-regulated-rather than up-regulated-in cells exposed to stress. Similarly, Izzotti et al also found that lung cells down-regulate a greater number of miRNAs when exposed to cigarette smoke (Izzotti et al 2009). Since stressed cells demand rapid protein translation, and miRNAs are known to repress translation, it is possible that cellular mechanisms may have evolved to reduce de novo miRNA synthesis during times of stress .…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…Last, we found that a greater number of miRNAs were down-regulated-rather than up-regulated-in cells exposed to stress. Similarly, Izzotti et al also found that lung cells down-regulate a greater number of miRNAs when exposed to cigarette smoke (Izzotti et al 2009). Since stressed cells demand rapid protein translation, and miRNAs are known to repress translation, it is possible that cellular mechanisms may have evolved to reduce de novo miRNA synthesis during times of stress .…”
Section: Discussionmentioning
confidence: 91%
“…However, several studies have previously reported that cells do in fact alter their miRNA expression profile when exposed to the following stressors: folate deficiency, arsenic exposure, radiation, hypoxia, and cigarette smoke (Marsit et al 2006;Kulshreshtha et al 2007;Weidhaas et al 2007;Izzotti et al 2009). Curiously, after comparing our results to those of previous studies, we unveiled three noteworthy findings: (1) several miRNAs (miR-125b, -222, -22, and let-7c) are expressed in response to most stressor types; (2) several TRMs (miR-452, -382, and -378) are only expressed by cells exposed to hyperthermia; and (3) cells primarily down-regulate miRNAs when exposed to stress (Table 3).…”
Section: Discussionmentioning
confidence: 99%
“…There are some reports of the effects of cigarette smoke on miRNA expression in tissues (De Flora et al, 2012). Exposure to cigarette smoke caused down-regulation of some miRNAs in mouse and rat lungs (Izzotti et al, 2009a(Izzotti et al, , 2009b, and the down-regulation in mouse lung was reversed by smoking cessation (Izzotti et al, 2011). Similar findings have been reported in humans; the levels of several miRNAs in airway epithelium (Schembri et al, 2009), placenta (Maccani et al, 2010, and alveolar macrophages (Graff et al, 2012) were lower in smokers than in non-smokers.…”
Section: Discussionmentioning
confidence: 99%
“…Previous work has shown that miR-143 and miR-145 expression levels are downregulated in rodent lungs exposed to cigarette smoke (which is a severe carcinogen) [46]. Additional studies have shown Brought to you by | MIT Libraries Authenticated Download Date | 5/9/18 9:15 AM that miR-143 and miR-145 have an inhibitory effect on lung cancer cell growth in both mice and humans [47].…”
Section: Tumor Suppressive Mirnas In Lung Cancermentioning
confidence: 99%
“…In humans, miR-143 and miR-145 are located on chromosome 5 [46]. Previous work has shown that miR-143 and miR-145 expression levels are downregulated in rodent lungs exposed to cigarette smoke (which is a severe carcinogen) [46].…”
Section: Tumor Suppressive Mirnas In Lung Cancermentioning
confidence: 99%